2016
DOI: 10.1111/codi.13105
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral transcutaneous tibial nerve stimulation for chronic constipation

Abstract: Bilateral transcutaneous tibial nerve stimulation appears to be effective in a quarter of patients with chronic constipation. Carefully selected patients with less severe disease may benefit more. This requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 47 publications
0
42
0
4
Order By: Relevance
“…Over 18 clinical studies have used the PAC-SYM, since its validation in 1999: 14 of these have been reported since 2010. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Moreover, these trials have examined a range of interventions including sacral nerve stimulation, 20 lifestyle changes 19 and pharmacological agents. 6,11 Historically, a reduction in total score of 1 point or more has been used as the cut-off to define a positive response to treatment, 2 implying that this is a meaningful improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Over 18 clinical studies have used the PAC-SYM, since its validation in 1999: 14 of these have been reported since 2010. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Moreover, these trials have examined a range of interventions including sacral nerve stimulation, 20 lifestyle changes 19 and pharmacological agents. 6,11 Historically, a reduction in total score of 1 point or more has been used as the cut-off to define a positive response to treatment, 2 implying that this is a meaningful improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Transcutaneous tibial nerve stimulation (TTNS) is reportedly beneficial for fecal and urinary incontinence. 7,8 A review of the literature showed that there are very few studies in which TTNS has been used and shown to be effective for constipation 9 however, there are practically no studies carried out exclusively on geriatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…Neuromodulation has recently been introduced for the treatment of FC, such as sacral nerve stimulation [ 5 ] and tibial nerve stimulation [ 6 ] with inconclusive results and largely unknown mechanisms. In a previous study, we reported a promising ameliorating effect of transcutaneous neuromodulation (TN) in FC patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%